2004
DOI: 10.1902/jop.2004.75.6.844
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Smoking With Vertical Periodontal Bone Loss

Abstract: The observations suggest that smoking is associated with increased levels of prevalence as well as severity of vertical bone loss. Smoking is considered a potential risk factor for vertical periodontal bone loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
35
0
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(43 citation statements)
references
References 23 publications
6
35
0
2
Order By: Relevance
“…The dose-response relationship was also suggested by the observation that the relative risk increased with increasing exposure. This observation confirms the evidence of previous studies concerning cigarette smoking (Bergström et al 1991, Haber & Kent 1992, Haber et al 1993, Grossi et al 1995, Bergström et al 2000a,b, Tomar & Asma 2000, Teng et al 2003, Baljoon et al 2004, 2005a, Bergström 2004, Razali et al 2005. This strength the association found in this cross sectional study.…”
Section: Tobacco Smoking Exposuresupporting
confidence: 93%
See 2 more Smart Citations
“…The dose-response relationship was also suggested by the observation that the relative risk increased with increasing exposure. This observation confirms the evidence of previous studies concerning cigarette smoking (Bergström et al 1991, Haber & Kent 1992, Haber et al 1993, Grossi et al 1995, Bergström et al 2000a,b, Tomar & Asma 2000, Teng et al 2003, Baljoon et al 2004, 2005a, Bergström 2004, Razali et al 2005. This strength the association found in this cross sectional study.…”
Section: Tobacco Smoking Exposuresupporting
confidence: 93%
“…The results indicated that the bone height was reduced in water pipe smokers as well as cigarette smokers compared to in non-smokers, suggesting that both smoking habits were associated with excess periodontal bone loss (Study III). This finding provided convincing evidence to support the role of tobacco smoking as a factor associated with periodontal bone height reduction and is in agreement with previous studies concerning cigarette smoking and periodontal bone loss of horizontal and vertical patterns (Bergström et al 1991, Grossi et al 1995, Persson et al 1998, Bergström et al 2000b, Baljoon et al 2004). …”
Section: Periodontal Bone Heightsupporting
confidence: 92%
See 1 more Smart Citation
“…Smoking promotes a high degree of ROS release that results in heightened oxidative damage to gingival tissues, periodontal ligaments (PDLs), and alveolar bone 4 . Previous studies have documented the effects of smoking including persistent gingival bleeding, 5 vertical bone loss, 6 and poor treatment outcomes 7 . Similarly, an in vitro study 8 showed that Nic had inhibitory effects on the attachment and growth of gingival and PDL fibroblasts.…”
mentioning
confidence: 99%
“…Con respecto a la pérdida dentaria, los pacientes que fuman pipa tienen un riesgo 1,6 veces mayor que los no fumadores, mientras que los que fuman cigarrillos tienen 1,3 veces más riesgo de perder dientes 24 . Se encontró que lo fumadores también tenían mayor cantidad de recesiones y adicionalmente sacos periodontales mas profundos comparado con los pacientes no fumadores 25 , además de tener mayor reabsorción ósea alveolar 26 y mayor prevalencia de defectos óseos verticales 27 . La evidencia indica que existe una respuesta inflamatoria diferente entre fumadores que presentan una evidente apariencia clínica fibrótica de los tejidos y menor cantidad de sitios con sangramiento al sondaje 28 .…”
Section: Efecto Sobre Los Tejidos Periodontalesunclassified